Skin Closure of Pfannenstiel Incision with Dermabond, Staples, or Suture during Cesarean Delivery: Experience of a Single Attending - Siddiqui, Danish S.; Lacuna, Eduardo M.; Chen, Han-Yang; Chauhan, Suneet P. (American Journal of Perinatology, 2013)
Objective We aimed to compare the rates of wound separation (WS) and surgical site infection (SSI) after cesarean delivery (CD) by a single surgeon. Pfannenstiel skin incision (PSI) was closed with Dermabond, staples, or suture.Study Design Retrospectively all women having CD via PSI were identified. WS and SSI rates with Dermabond were compared with other two techniques.Results Of 239 CDs performed, 88% (n = 211) were available for postpartum evaluation. The PSI was closed with Dermabond in 85 (40%), staples in 76 (36%), and suture in 50 (24%). Overall WS rate was 7%; with Dermabond, it was 5% versus 13% with staple (p = 0.090) and 2% with suture (p = 0.651). Post hoc calculation suggests a randomization of 4325 women is needed to determine if Dermabond has one-third less wound complication than suture.Conclusion For the PSI closure, Dermabond may be a useful alternative skin closure device, though a randomized trial is warranted.
Keywords: skin closure; Dermabond; staples; suture; cesarean delivery